Awareness of 'Systolic Anterior Motion' in Different Conditions. Issue 12 (6th January 2018) - Raut, Monish; Maheshwari, Arun; Swain, Baryon
Perioperative echocardiography, especially transesophageal echocardiography, is of paramount importance in evaluating and managing refractory hypotension, a potential cause of which is systolic anterior motion (SAM) of anterior mitral leaflet. Dynamically moving anterior mitral valve leaflet towards the left ventricular outflow tract (LVOT) is described as SAM. Although SAM was initially observed in patients with hypertrophic cardiomyopathy, it can also be seen in patients with complex dynamic anatomy of the left ventricle. Interestingly, SAM may or may not give rise to clinically significant LVOT obstruction. Hence, it is of paramount importance for perioperative physician to know such 'dynamic SAM' which can potentially and significantly affect and alter perioperative management.